The king's speech - Hooper, Tom, 1972-; Firth, Colin, 1960-; Rush, Geoffrey, 1951-; Bonham Carter, Helena, 1966- (Beverly Hills, CA : Anchor Bay Entertainment/Weinstein Company, 2011)
After inheriting the throne when his brother abdicates from it, King George VI hires a speaking coach to help him with a stuttering problem so he can confidently lead his kingdom.
Originally released as a motion picture in 2010.
Features: commentary with director Tom Hooper, Q & A with the director & the cast including Colin Firth, The real Lionel Logue highlights, Speeches from the real King George VI, An inspirational story of an unlikely friendship.
Colin Firth, Geoffrey Rush, Helena Bonham-Carter, Guy Pearce, Jennifer Ehle.
MPAA rating: R.
DVD.
Keywords: George -- VI, -- King of Great Britain, -- 1895-1952 -- Drama; Kings and rulers -- England -- Drama; Speech therapy -- Drama; Speech therapists -- Drama; Fiction films; Feature films; Biographical films; Historical films